Konsep Zuhud dalam Ajaran Tasawuf Di Era Modern Menurut Pandangan Ulama - Bambang Agus Setiyawan; Khusnul Khotimah (Jurnal Ilmiah Islamic Resources, 2022)
In this modern era, almost all fields of life, be it cultural, economic, social and religious, cannot escape the influence of modernization as a form of advanced civilization which actually has such a complex impact. Advances in technology gave birth to various conveniences in human life. However, on the other hand, progress also shifts values in life. As a result, human life becomes spiritually dry, even faith in the Almighty has also begun to fade. Psychological problems such as stress, anxiety, confusion, and so on often approach modern human life. Then the solution is to return to religious teachings through Sufism. Sufism is a way to fight the absurdity of human life. The essence of Sufism is the awareness of communication with God. The initial phase of entering Sufism is zuhud. The method in this study is a qualitative method with a descriptive approach. The method of collecting data in this study is through observation, interviews, and documentation of religious leaders/ulama in Banyumas Regency. The significance of the concept of zuhud in modern life: first, narrowing the will of the heart to be enslaved by the world and matter, second, as a drop of fresh water for the problems of the spirituality of modern life which are increasingly drying up from the value of divinity, third, as a foundation in responding to temporary life and pathomorganna, which always decorated with material, the fourth is as akhlakul karimah which gives birth to wisdom in pursuing the life of the world and in preparing for life after death and the last is as a concept in practicing social behavior in accordance with the Islamic concept of helping each other in goodness